Learnings from a decade experience of a community-based HIV and STI testing and counseling center in Lisbon – Portugal. (30th September 2020) - Fernandes, F; Meireles, P; Rocha, M; Duque, M; Barros, H
Abstract: Background: In the context of an increased number of men who have sex with men (MSM) being diagnosed with HIV infection in many European countries, it became a matter of maximum priority to consider new strategies to monitor and tackle the epidemic. In this scenario, CheckpointLX and a cohort study were projected as a sexual health and research center oriented towards MSM in Portugal. Methods: In 2011 CheckpointLX was launched in Lisbon as a community-based center for anonymous and free rapid HIV and other sexually transmitted diseases (STI) testing with a strong component of counseling for sexual health, specially targeted at MSM. In the case of a reactive test, a medical appointment is proposed and scheduled. The Lisbon Cohort of MSM is an ongoing observational prospective study conducted at CheckpointLX. Collected data include sexual behaviors, preventive strategies, and history of STI. Results: Until July 2019, 7, 351 HIV-negative MSM chose to participate in the Lisbon Cohort of MSM. 3, 523 had at least one follow-up visit. The median age was 29 (IQR 25 - 37), and 27% were born in a foreign country, including 15% born in Africa and South America. HIV incidence increased up until 2015, reaching 5 reactive tests per 100 tested annually. There has been a sustained decrease in HIV observed since 2015. The use of HIV prevention tools was provided: 31% used condoms consistently, 3% reported PrEP, and 4% PEP. Conclusions: A decade since the beginning of this experience shows positive results, such as increased access and testing. We promoted a stigma-free service that facilitated MSM's and other key population's access to sexual health care. We contribute unique data for assisting in the monitoring of the Dublin Declaration in Portugal.